The Impact of E-Marketing Technology in Improving The Effectiveness of Communication with Customers: A Case of Attayibat International Trading - Alsabahi, Rabea Rashed Mansoor; Ridanasti, Erlita (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2024)
In today's digital age, customer prioritization is at the heart of effective digital marketing strategies. This study delves into the complex dynamics between using digital tools and promoting meaningful electronic communication with customers. Key factors such as customer orientation, transaction security, response efficiency, ease of communication, and customization were comprehensively studied through a comprehensive survey of several customers on Al Tayebat Trading Company’s website. The findings highlight how these elements significantly shape customer interactions in the digital realm. Ultimately, the research underscores the pivotal role of customer-focused e-marketing practices in enhancing electronic communications and promoting strong customer engagement.